Gap Analysis in workforce and infrastructure in the subcenters for upgradation to health and wellness center in a community development block of purba Bardhaman district, West Bengal - Prosun Goswami; Amitava Chakraborty; Dilip Kumar Das; Soumalya Ray (Wolters Kluwer Medknow Publications, 2021)
Context: The government of India has recently decided to upgrade subcenters (SCs) to health and wellness centers (HWCs) for providing comprehensive quality services. Aims: The present study was undertaken to determine workforce- and infrastructure-wise gaps in the SCs for upgradation to HWCs and assess knowledge of the auxiliary nurse midwives (ANMs) regarding services to be delivered through HWCs. Settings and Design: This cross-sectional study was conducted in Bhatar block of Purba Bardhaman district between August and October 2019. Subjects and Methods: Workforce and infrastructure availability was assessed using a checklist in 38 SCs and knowledge was assessed using a questionnaire among ANMs. Statistical Analysis Used: Data entry and analysis was done in Microsoft™ Excel™. Results: No Subcentre had Community Health Officer and 23.7% of Subcentre were without second ANM. 28.9% of the ANMs had adequate knowledge about services to be delivered through HWCs. Infrastructurally, lack of staff residential facility (76.3%), water supply (34.2%), and inadequate civil construction (34.2%) were major barriers. Conclusions: Adequate recruitment of HCWs, infrastructure upliftment, and proper training of HCWs in the SCs are the need of the hour.